Experience of Nepali Indigenous Peoples on Free, Prior and Informed Consent (FPIC) - Sherpa, Pasang D; Rai, Tunga B (Journal of Forest and Livelihood, 2013)
DOI: http://dx.doi.org/10.3126/jfl.v11i2.8626 Journal of Forestry and Livelihood Vol.11(2) 2013 82-86